Características fenotípicas e genéticas relacionadas à Brazilian Klebsiella carbapenemase - BKC-1 - Martins, Willames Marcos Brasileiro da Silva [UNIFESP] (2018)
Klebsiella pneumoniae is a widely reported pathogen causing different types of infections, which has been highlighted by the increased levels of antimicrobial resistance. Among the mechanisms of resistance, the production of carbapenemases has a significant clinical impact since infections caused by carbapenem-resistant K. pneumoniae can lead to the outcome of infected patients. The objective of this study was to determine the microbiological and genetic characteristics of BKC-1 -producing bacterial isolates. The present thesis was subdivided into five articles made during the doctorate period. Article 1: BKC-1 is a new class A carbapenemase. It was recently reported in K. pneumoniae clinical isolates collected from the State of São Paulo. This study aimed to investigate the frequency of in clinical isolates of Klebsiella spp. harboring blaBKC-1.Six hundred and thirty-seven clinical isolates of Klebsiella spp. from hospitals located in the five Brazilian regions were investigated. Among them, only two were identified as BKC-1 producers. These isolates were also detected in hospitals located in the State of São Paulo, and belonged to ST442 and ST1781, respectively, which were grouped under CC442. The isolates presented the multi-drug resistant phenotype, with the presence of different resistance mechanisms. One of these isolates was resistant to polymyxins due to mgrB disruption by an IS. Both strains carried a small plasmid, which was identical to the original plasmid described in 2015. Article 2: Due to weak hydrolytic activity of BKC- 1 towards carbapenems, this study was carried out to compare the performance of distinct phenotypic test for detection of BKC-1-producing isolates. Traditional tests such as THM, DDST-AFB were not able to detect the production of this carbapenemase among the isolates tested. In contrast, the colorimetric tests Carba- NP, Blue-carba and Carbapenembac were able to detect such isolates as carbapenemase producers. More laborious tests such as detection of hydrolysis by MALDI-TOF MS and spectrophotometry showed good performance for detecting BKC-1 activity. Article 3: Based on the manuscript published by Partridge (2016), article 3 was written. It is a response letter to the genetic findings proposed by the Partridge regarding to the association among blaBKC-1, aph3a-VI and ISKpn23. Article 4: Due to the lack of knowledge of the genetic mechanisms involved in the acquisition and mobilization of blaBKC-1, mobilization (conjugation and transposition) and expression experiments were performed with the objective of determining the role of ISKpn23 in mobilization and expression of the blaBKC-1. The experiments demonstrated that ISKpn23 was able to modulate the expression of the blaBKC-1, contributing to the increase of the β-lactam MICs. On the other hand, ISKpn23 did not modulate aph3a-VI expression. Additionally, experiments evidenced the mobilization ability of pA60136 by conjugation, but did not to elucidate how the blaBKC- 1 was genetically engineered. Article 5: Despite the rare reports of isolated BKC-1 producers in Brazil, the objective of this study was to report the silent spread of a BKC-1 producing K. pneumoniae ST442 clone as well as the acquisition of blaBKC-1 by a hypervirulent K. pneumoniae clone, ST11. These isolates were characterized microbiologically. This dissemination occurred in a university hospital located in the city of São Paulo for approximately 3 years (2010-2012). In this period, 16 isolates producers of BKC-1 were recovered with the presence of a majorities clone (A1 / ST442; in 15 isolates) belonging to ST442. In six of the sixteen isolates the coproduction of BKC-1 and KPC-2 was identified.